2022
DOI: 10.1021/acs.jchemed.2c00188
|View full text |Cite
|
Sign up to set email alerts
|

When All You Have Is a Covalent Model of Bonding, Every Substance Is a Molecule: A Longitudinal Study of Student Enactment of Covalent and Ionic Bonding Models

Abstract: This longitudinal study examines the responses of students at two different institutions to creative exercises related to models of chemical bonding. Questions in the form of creative exercises required students to provide relevant, accurate, and distinct statements about two compounds for which they were provided only the formula and electronegativity values: SCl 2 and CaCl 2 . Students responded to the questions at the end of general chemistry, six months later, and one year later. Their responses were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Demonstrated by Teachers 106,110,and 206, there is a pedagogical tendency to apply chemistry symbols in situations that necessitate particulate-level reasoning for redox conceptual understanding. This ''square peg in a round hole'' scenario parallels how students routinely used a covalent model for determining ionic compounds (Bowe et al, 2022). In addition, Schafer et al (2023) provided evidence that curricular materials embody certain epistemological messages that inform processes of teaching and learning.…”
Section: For Researchersmentioning
confidence: 71%
“…Demonstrated by Teachers 106,110,and 206, there is a pedagogical tendency to apply chemistry symbols in situations that necessitate particulate-level reasoning for redox conceptual understanding. This ''square peg in a round hole'' scenario parallels how students routinely used a covalent model for determining ionic compounds (Bowe et al, 2022). In addition, Schafer et al (2023) provided evidence that curricular materials embody certain epistemological messages that inform processes of teaching and learning.…”
Section: For Researchersmentioning
confidence: 71%
“…That said, a number of studies have also explored creative exercises from a qualitative lens. ,,,, Much of the current qualitative inquiries on creative exercises have centered around response analysis and open-ended surveys on student experiences of the exercises. ,,,, The exploration of student experiences with creative exercises in later studies was consistent with the earlier literature in that the exercises were generally viewed in a positive light, though students did note anxiety when first encountering creative exercises . As for the analysis of student responses, researchers found that students were linking prior knowledge with current topics which varied across the semester. ,, …”
Section: Introductionmentioning
confidence: 99%
“…16 That said, a number of studies have also explored creative exercises from a qualitative lens. 6,11,16,18,21 Much of the current qualitative inquiries on creative exercises have centered around response analysis and open-ended surveys on student experiences of the exercises. 6,11,16,18,21 The exploration of student experiences with creative exercises in later studies was consistent with the earlier literature in that the exercises were generally viewed in a positive light, though students did note anxiety when first encountering creative exercises.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, students often fail to differentiate between the symbol H 2 O, which refers to a molecular entity, and the symbol H 2 O­(l), which refers to a macroscopic chemical substance. , Thinking of the representation H 2 O­(l) as corresponding to a chemical entity at the molecular rather than the macroscopic levels (granularity issue) may reinforce the intuitive belief that molecules have macro-like properties. , The same type of intuitive reasoning may be prompted when thinking of the colors used to represent different types of atoms as iconic rather than symbolic cues (iconicity issue) . Similarly, assuming that the symbol NaCl corresponds to a molecular rather than an ionic entity (granularity and dimensionality issues) will affect inferences about the structure and properties of the chemical entity to which it refers. , Considering that the different colors in an electrostatic potential map are indicative of variations in temperature or heat rather than in electric potential (dimensionality issue) will constrain reasoning about intermolecular interactions . Thinking of reaction progress in an energy diagram as a measure of time rather than conversion progress along a reaction pathway (dimensionality issue) will affect reasoning about relative reaction rates .…”
Section: Introductionmentioning
confidence: 99%
“… 56 Similarly, assuming that the symbol NaCl corresponds to a molecular rather than an ionic entity (granularity and dimensionality issues) will affect inferences about the structure and properties of the chemical entity to which it refers. 57 , 58 Considering that the different colors in an electrostatic potential map are indicative of variations in temperature or heat rather than in electric potential (dimensionality issue) will constrain reasoning about intermolecular interactions. 59 Thinking of reaction progress in an energy diagram as a measure of time rather than conversion progress along a reaction pathway (dimensionality issue) will affect reasoning about relative reaction rates.…”
Section: Introductionmentioning
confidence: 99%